Perancangan Sistem Informasi Koperasi Syariah Berbasis Web - Riri Safitri (JURNAL TEKNIK INFORMATIKA, 2019)
Jampang Village is one of the villages assisted by the Lembaga Amil Zakat Al Azhar  Peduli Umat (LAZ APU) in the form of Kelompok Swadaya Masyarakat (KSM). The people in Jampang village have various jobs, including fish farmers, broiler breeders, doorman craftsmen, plant seed sellers and others. The Foundation provides funding or capital assistance to the community through a sharia microfinance institution that collects and distributes public funds in accordance with Islamic law. Koperasi Syariah Desa Jampang is currently still operating manually. Registration process, member information, amount of funds and reports are still done manually and stored in a notebook. This causes the operational process not to run properly, because the data is not organized and stored neatly. Based on the above conditions, a financial information system is designed that is a web-based Islamic cooperative, so that the operational processes and reports to members and administrators can run better and faster. Information systems are designed using SDLC through the stages of user requirements and analysis. With this method, it is expected that information systems are designed according to user needs.